2004
DOI: 10.1021/ja0461116
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Observations of Water Production and Distribution in an Operating H2/O2PEM Fuel Cell Assembly Using1H NMR Microscopy

Abstract: Proton NMR imaging was used to investigate in situ the distribution of water in a polymer electrolyte membrane fuel cell operating on H2 and O2. In a single experiment, water was monitored in the gas flow channels, the membrane electrode assembly, and in the membrane surrounding the catalysts. Radial gradient diffusion removes water from the catalysts into the surrounding membrane. This research demonstrates the strength of 1H NMR microscopy as an aid for designing fuel cells to optimize water management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
83
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(85 citation statements)
references
References 24 publications
1
83
0
1
Order By: Relevance
“…We quickly realized, however, that 1 H NMR microscopy can provide unique information regarding the spatial distribution of water throughout an operating PEMFC. [46] Quantitative measurements of the internal dimensions of the PEMFC are readily obtained by filling the assembly with H 2 O(l). Shown in Figure 6 are two 1 H NMR microscopy images of the water-filled PEMFC obtained using a spin-echo experiment.…”
Section: H Nmr Microscopy Of An Operating Pemfcmentioning
confidence: 99%
See 1 more Smart Citation
“…We quickly realized, however, that 1 H NMR microscopy can provide unique information regarding the spatial distribution of water throughout an operating PEMFC. [46] Quantitative measurements of the internal dimensions of the PEMFC are readily obtained by filling the assembly with H 2 O(l). Shown in Figure 6 are two 1 H NMR microscopy images of the water-filled PEMFC obtained using a spin-echo experiment.…”
Section: H Nmr Microscopy Of An Operating Pemfcmentioning
confidence: 99%
“…These methods include electron paramagnetic resonance (EPR) investigations of PEM degradation, [29,30] the construction of PEMFCs using transparent materials, [31][32][33][34][35][36][37][38][39] the use of neutron imaging, [40][41][42][43][44][45] and 1 H NMR microscopy. [46][47][48][49][50] For example, numerous studies have used transparent PEMFCs to investigate the formation of CO 2 (g) in the anode flow field of direct methanol fuel cells [31,32] and the behavior of water in gas diffusion layers. [33] Neutron imaging techniques are inherently sensitive to protons, whilst insensitive to many materials typically used for constructing fuel cells (for example, Al, graphite).…”
mentioning
confidence: 99%
“…However, information about methanol crossover and the related phenomena occurring in the polymer electrolyte membranes (PEMs) of operating DMFCs is scarce, which can be mainly attributed to the difficulty of directly studying the methanol behavior. Recently, nuclear magnetic resonance (NMR) techniques were successfully employed to probe water production and distribution in PEM fuel cells (PEMFC) [4] as well as water and methanol transport in DMFCs.[5] Herein, we present a new type of membrane electrode assembly (MEA) from which a PEM can be extracted free from electrode components, such as catalysts, carbon black, and carbon cloth. Solid-state magic-angle spinning NMR (MAS NMR) studies of this PEM allowedfor the first time-the direct detection of methanol and the reaction intermediates traveling through the PEM during fuel-cell operation.…”
mentioning
confidence: 99%
“…Similarly, Zhang et al [66] reported a direct water content measurement across the Nafion membrane in an operational PEMFC, employing double half k-space spin echo single point imaging techniques. Feindel and co-workers [70][71][72][73] performed systematic in-situ investigations of in-plane water distributions and accumulation in the PEM. For example, 1 H NMR microscopy was employed to investigate the influence of co-versus counter-flow gas configurations on the in-plane distribution of water in PEM of the operating PEMFC.…”
Section: Nuclear Magnetic Resonance (Nmr) Imagingmentioning
confidence: 99%